Treatment of the twin-twin transfusion syndrome: initial experience using laser-induced interstitial thermotherapy - Sohn, Christof; Wallwiener, Diethelm; Kurek, Raffael; Hahn, Uwe; Schießer, Monika; Bastert, Gunther (Fetal diagnosis and therapy, 1996)
This paper describes our initial experience with laser-induced interstitial thermotherapy (LITT) for the treatment of the twin-twin transfusion syndrome (TTTS). This procedure was utilized in four pregnancies - three monochorionic twin pregnancies and one triplet pregnancy (20-26 weeks of gestation) - with severe TTTS with fetal dropsy, polyhydramnion of the acceptor, and anhydramnion of the donor. In vitro examinations of placental tissue had shown that laser coagulation can be monitored by sonography, hence we used this method for the first time in these four pregnancies. Blood vessels connecting the two umbilical cords were determined prior to the treatment using a new ultrasound color technique which is highly sensitive and capable of representing slow blood flow velocities. A 1.2 mm thick puncture needle was then directed to the shunt under on-line ultrasound control. All patients had an anterior wall placenta. The laser fiber was inserted via this thin needle. A coagulation time of 2-3 min was necessary at 3 W. In the one twin pregnancy the intrauterine fetal death of the smaller child occurred 10 weeks after LITT, the other child survived and is healthy. A cesarian section was necessary in another twin pregnancy 1 week after LITT due to the intrauterine death of the smaller child. In the third twin pregnancy, the donor, who had already had distinct bradycardia prior to the treatment, died immediately after LITT. The intrauterine fetal death of the donor in the triplet pregnancy occurred 3 days after LITT once the volume of amniotic fluid had basically returned to normal. The tragic intrauterine death of the uninvolved child occurred 13 weeks later as a result of umbilical cord strangulation, the surviving child is healthy. All four pregnancies were severe and advanced cases of TTTS with a very poor prognosis, leaving us with no other alternative to the described method of treatment. The instruments we used are a lot thinner than those utilized for fetoscopic laser treatment to date. Furthermore, it is not necessary to penetrate the amniotic sac in patients with an anterior wall placenta; intraplacental vessels can be coagulated, and the laser energy required for LITT is also much lower. In our opinion these advantages justify the utilization of LITT under more promising conditions than those described above.